PROFIL ELEKTRONIK WARUNG GOTONG ROYONG (E-WARONG) KUBE PKH SEBAGAI ALTERNATIF PENANGGULANGAN KEMISKINAN DI PROVINSI SULAWESI TENGGARA - Akhmad Marhadi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This research aims at indentifying the profile of e-Warong KUBe PKH as an alternative on poverty alleviation in Southeast Sulawesi. This research uses descriptive qualitative approach, and uses Focus Group Discussion, field observation and in depth interview as techniques of data collection. The results show that: a) 25 e warong KUBE PKH in Southeast Sulawesi province doesn’t have optimal function. Generally, E-Warong only serves as a place to sell staple food only, but other functions have not run optimally as mandate of Social Minister Regulation Number 25 of 2016; b) all e-Warong has fulfilled the requirements of the establishment of the Social Minister Regulation; c) The use of EDC can only be done by 12 e-Warong in Bau-Bau City; d) all e-Warong have membership characteristics that have been accorded with Social Minister regulation; e) the whole e-Warong in Baubau city uses BPSU funds and KUBE grants according to their allocation. While the use of funds by e-Warong in Kendari City has not been optimal; f) the basic supply of food is supplied by e-Warong is now generally obtained from non-bulog suppliers, from wholesale grocery stores found in Bau-Bau and Kendari municipalities; and g) all e-Warong has not been able to serve the disbursement of non-cash social assistance funds.